Physiotherapy Management in Cases of Spasticity Hemiparese Sinistra ec Ischemic Cerebrovascular Accident a Case Report - Zulfatirrohman, Atikah Itsna; Naufal, Adnan Faris; Nasuka, Muhammad (Universitas Muhammadiyah Surakarta, 2023)
A cerebrovascular accident or often referred to as a stroke is a clinical condition that occurs when the circulation of blood flow to the brain is disrupted due to a blockage of blood vessels or due to bleeding. The problem in this case is related to the low LGS value as measured using a goniometer, reduced muscle strength using the MMT value, related to the balance value as measured using the berg balance scale, there is pain as measured using the NRS value and the presence of spasticity as measured by using the Asworth scale, as well as decreased functional ability with the Barthel index and incorrect gait patterns. The physiotherapy intervention given in this study is by giving Infrared, Core stability exercise, Exercise therapy, and Gait Retraining Exercises. This research method uses a case report. The result is an increase in the value of LGS, MMT, berg balance scale, and there is a reduction in the value of pain, spasticity and improvement in gait patterns. But there is no change in the value of functional ability.